High-frequency kernel in the algorithm of function restoration from the projections for diverging beams - Tarasenko-Zelenaya , L. I.; Zavarin , A. N.; Radvansky , S. L. (Ukrains’kyi Matematychnyi Zhurnal, 1988)
-